Employing Polar Solvent Controlled Ionization in Precursors for Synthesis of High‐Quality Inorganic Perovskite Nanocrystals at Room Temperature. (10th January 2018) - Fang, Fan; Chen, Wei; Li, Yang; Liu, Haochen; Mei, Ming; Zhang, Ruan; Hao, Junjie; Mikita, Marus; Cao, Wanqiang; Pan, Ruikun; Wang, Kai; Sun, Xiao Wei
Abstract: All inorganic cesium lead halide (CsPbX3, X = Cl, Br, I) perovskite nanocrystals (PeNCs) are synthesized by employing polar solvent controlled ionization (PCI) method in precursors. The new strategy can be easily carried out at room temperature and allow to employ smaller amount of weaker polarity and a broader range of low‐boiling low‐toxic solvents. The as prepared CsPbX3 PeNCs reveal tunable emission spectra from 380 to 700 nm and high quantum yields over 80% with narrow full width at half maximum (FWHM). Meanwhile, larger "effective Stokes shifts" of PeNCs in PCI method, which enlarges 200% more than other PeNCs in regular methods, are observed. Most interestingly, the PeNCs growth process is coupling with some typical crystals formations. The main morphologies of CsPbI3 PeNCs are hybrid of nanorods and nanoparticles. The primary morphologies of CsPbBr x I3‐ x and CsPbBr3 PeNCs are nanowires, which are supposed to have great potentials for applying in laser arrays and highly sensitive photodetector applications. Furthermore, such superior optical is endowed to fabricate white light emitting diodes, which has wide color gamut covering up to 120% of the National Television Systems Committee color standard. Abstract : All inorganic cesium lead halideperovskite nanocrystals (PeNCs) are synthesized by a new strategy employing a polar solvent controlled ionization method. The as prepared PeNCs reveal tunable emission spectra, high quantum yields, narrow emission, and large "effective Stokes shifts." Most interestingly, the PeNCs growth process is coupling with some typical crystals formations, including nanoparticles, nanorods, and nanowires.